2-Hydroxyglutarate produced by neomorphic IDH mutations suppresses homologous recombination and induces PARP inhibitor sensitivity - Sulkowski, Parker L; Corso, Christopher D; Robinson, Nathaniel D; Scanlon, Susan E; Purshouse, Karin R; Bai, Hanwen; Liu, Yanfeng; Sundaram, Ranjini K; Hegan, Denise C; Fons, Nathan R; Breuer, Gregory A; Song, Yuanbin; et al. (Science translational medicine, 2017)
2-Hydroxyglutarate (2HG) exists as two enantiomers, (R)-2HG and (S)-2HG, and both are implicated in tumor progression via their inhibitory effects on α-ketoglutarate (αKG)-dependent dioxygenases. The former is an oncometabolite that is induced by the neomorphic activity conferred by isocitrate dehydrogenase 1 (IDH1) and IDH2 mutations, whereas the latter is produced under pathologic processes such as hypoxia. We report that IDH1/2 mutations induce a homologous recombination (HR) defect that renders tumor cells exquisitely sensitive to poly(adenosine 5'-diphosphate-ribose) polymerase (PARP) inhibitors. This "BRCAness" phenotype of IDH mutant cells can be completely reversed by treatment with small-molecule inhibitors of the mutant IDH1 enzyme, and conversely, it can be entirely recapitulated by treatment with either of the 2HG enantiomers in cells with intact IDH1/2 proteins. We demonstrate mutant IDH1-dependent PARP inhibitor sensitivity in a range of clinically relevant models, including primary patient-derived glioma cells in culture and genetically matched tumor xenografts in vivo. These findings provide the basis for a possible therapeutic strategy exploiting the biological consequences of mutant IDH, rather than attempting to block 2HG production, by targeting the 2HG-dependent HR deficiency with PARP inhibition. Furthermore, our results uncover an unexpected link between oncometabolites, altered DNA repair, and genetic instability.